Collaborative Governance of Urban Flood Management: A Study in Surabaya City, Indonesia - Holilah, Holilah; Muyassar, M. Zainur Rizky; Zamani, Muhammad Hafaz (SIYAR Journal, 2026)
: Flooding remains a persistent challenge in rapidly urbanizing cities, including Surabaya, Indonesia. This study examines the application of democratic collaborative governance in urban flood management by analyzing how multi-stakeholder collaboration enhances sustainable flood mitigation. Guided by Ansell and Gash’s Collaborative Governance framework, the research investigates the interactions among local government, non-governmental organizations, the private sector, and local communities. A descriptive qualitative approach was employed through interviews, observations, and document analysis involving key stakeholders from the Surabaya Water Resources and Public Works Agency (DSDABM), the Regional Disaster Management Agency (BPBD), the Regional Representative Council (DPRD), and flood-affected residents. The findings indicate that Surabaya has strengthened flood governance through effective political leadership, institutional coordination, and participatory mechanisms such as the 112 Command Center and musrenbang (participatory development planning). These initiatives have improved emergency response, preparedness, and community engagement while supporting the localization of Sustainable Development Goals (SDGs), particularly SDG 11 (Sustainable Cities and Communities) and SDG 13 (Climate Action). However, challenges persist, including limited public awareness, technical constraints, extreme weather events, and socio-political barriers that reduce collaborative effectiveness. The study concludes that integrating democratic principles into collaborative governance enhances inclusiveness, accountability, and urban resilience, offering practical lessons for other cities seeking adaptive and sustainable approaches to flood management.